The effect of flux diverters on the AC loss of REBCO coil coupled with iron core. (December 2022) - Chen, Wei; Jin, Rong; Wang, Shuxin; Xu, Minghai; Che, Tong; Shen, Boyang; Yang, Xinsheng; Zhao, Yong
Highlights: The total AC loss of the coil assembly of the coupled iron core is greater than that of the uncoupled iron core coil. At a lower transport current, the iron loss introduced by the flux diverter will increase the AC loss of the coil assembly. At a higher transport current, the flux diverter plays a positive role in reducing the AC loss of the coil assembly. Abstract: High temperature superconducting (HTS) coil coupled with iron core can be widely used in superconducting power equipment such as superconducting motor, superconducting current limiter, superconducting transformer and so on. The AC loss of HTS coil decreases the efficiency and reliability of superconducting machines, and also brought severe challenges to the cryogenic system. The introduction of iron core will have a negative impact on the AC loss of superconducting coil, and the iron core itself will also produce iron loss, which will affect the overall efficiency of the system. It is considered that the additional flux diverter at the end of the coil can effectively reduce the AC loss of the coil. However, whether this method is effective for the HTS coil coupled with iron core has not been studied. Therefore, this paper focuses on the influence of flux diverter on the AC loss of HTS coil coupled with iron core by H -formulation. The results show that the iron loss of flux diverter plays a leading role in the coil assembly at low transport current, and the introduction of flux diverter plays a positive role in reducing the total AC loss of coil assembly at high transport current.